2023
DOI: 10.3390/vaccines11030576
|View full text |Cite
|
Sign up to set email alerts
|

Encephalitis following COVID-19 Vaccination: A Systematic Review

Abstract: Background: Since the advent of global COVID-19 vaccination, several studies reported cases of encephalitis with its various subtypes following COVID-19 vaccinations. In this regard, we conducted a systematic review to investigate and characterize the clinical settings of these reported cases to aid in physician awareness and proper care provision. Methods: We systematically searched PubMed, Web of Science, and Scopus and manually searched Google Scholar. Studies published until October 2022 were included. Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
(38 reference statements)
3
14
0
Order By: Relevance
“…the occurrence after the first or, less frequently, the second dose in most of the patients, as previously described ( 17 , 19 , 42 ) and, again, in line with the mechanistic hypothesis of these disorders;…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…the occurrence after the first or, less frequently, the second dose in most of the patients, as previously described ( 17 , 19 , 42 ) and, again, in line with the mechanistic hypothesis of these disorders;…”
Section: Discussionsupporting
confidence: 88%
“…(7-11 days) ( 16 ), Abdelhady et al. (9.97 days) ( 42 ), Jarius et al. (13 days) ( 36 ), Asioli et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, seizures could be caused by induction of glutamate release and inhibition of the release of inhibitory neurotransmitters, triggered by proinflammatory cytokines in the brain, as also happens in SARS-CoV-2 infection . Furthermore, SARS-CoV-2 vaccines could result in autoimmune encephalopathy, which is commonly associated with seizures …”
Section: Discussionmentioning
confidence: 99%
“…They showed that covid-19 vaccine can induce acute transverse myelitis, MS, acute demyelinating encephalomyelitis (ADEM), and neuromyelitis optica spectrum disorder (NMOSD) [ 152 ]. Moreover, Abdelhady et al reported 65 patients who developed encephalitis following covid-19 vaccines [ 153 ]. Despite first presentation of MS after covid-19 vaccine was reported in some studies [ 154 157 ], Stefanou et al showed that Covid-19 vaccination is not associated with increasing the risk of relapse of patients with MS irrespective to the type of covid-19 vaccines [ 158 ], and therefore, most of the patients with MS are willing to receive covie-19 vaccine [ 159 ].…”
Section: Methodsmentioning
confidence: 99%